If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -17 = -17 + z Reorder the terms: -17 + 6z = -17 + z Add '17' to each side of the equation. -17 + 17 + 6z = -17 + 17 + z Combine like terms: -17 + 17 = 0 0 + 6z = -17 + 17 + z 6z = -17 + 17 + z Combine like terms: -17 + 17 = 0 6z = 0 + z 6z = z Solving 6z = z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 6z + -1z = z + -1z Combine like terms: 6z + -1z = 5z 5z = z + -1z Combine like terms: z + -1z = 0 5z = 0 Divide each side by '5'. z = 0 Simplifying z = 0
| 8-7x=68-28 | | 6x+8y=1/10 | | 4x+14=42-10x | | x+(1/5)x=30 | | -24-3x=13-9x | | 8(7)-3(-2)=3 | | 8(7)-33(-2)=3 | | 30-.20= | | 2(r-.02)=1.5r | | 5lnx=-3 | | (6t+1)/9=((t+16)/18)+(t-2)/18 | | 9(-63)+7y=63 | | 3(9x-5)= | | 12-6x=12-2x | | 9x+7(0)=63 | | 9(0)+7y=63 | | 5x+8=7x+24 | | -[2n-(-7)]= | | -18+[-(-13)]= | | 2x+9(-90)=90 | | X+4=18-x | | -9x-2.4=4x | | X+4=18-4 | | -(-3+4)= | | 2(-90)+9y=90 | | 2x+9(0)=90 | | 2(0)+9y=90 | | 7-[(-8)+(-2)]= | | -x-41=-3x-9 | | a-2b=32 | | 5-2x=4x-19 | | 9x+4=15x-9 |